Histopathological assessment in cases with gluten-sensitive enteropathy: Significance of typing - Sibel ÖZTÜRK; Ebru SERİNÖZ and Tülay KEKLİK and Arzu ENSARİ and Işınsu KUZU and Aydan KANSU and Buket ALTUNTAŞ and Hülya ÇETİNKAYA and; ÖZDEN (Turkish Journal of Gastroenterology, 2019)
-